Predicting Psychological Well-being Based on Family Emotional Atmosphere: Mediating Role of Social Support - Zahra Dolati; Beheshteh Niusha; Fatemeh Shaterian Mohammadi (Iranian Journal of Educational Research)
Objective: The primary aim of the present study was to ascertain the role of social support as a mediator in the association between the emotional climate within the family and the psychological well-being of individuals who have been discharged from Tehran hospitals following their battle with the Covid-19 disease. Methods: The research employed structural equation modeling as its methodology, with the statistical population consisting of all individuals who had been discharged from Tehran hospitals due to Covid-19 between the years 2021 and 2022. Among this population, a sample of 400 individuals was selected using accessible and purposive sampling techniques. Data collection was conducted through the utilization of the short form of the psychological well-being questionnaire (Reif, 1989), the family emotional climate questionnaire (Hillburn, 1964), and the multidimensional scale of perceived social support (Zimmet et al., 1988). Data analysis was carried out employing the structural equation modeling method in AMOS 24 and SPSS 26 software. Results: The findings of the study indicated that the emotional atmosphere within the family has a positive impact on both social support and the psychological well-being of patients who have been discharged from the hospital after being affected by Covid-19. Moreover, social support was found to have a positive and significant influence on the psychological well-being of these patients. Further analysis of the mediation effect revealed that social support plays a mediating role in the relationship between the emotional atmosphere within the family and psychological well-being. Conclusion: The results of this study provide support for the importance of attending to the psychological state of patients following hospital discharge and for the provision of social support and a positive emotional climate within the family as means of enhancing their psychological well-being.